ANALYSIS OF YOGURT CERTIFICATION PROCEDURE - Umidjon Karimov; Todjiddinova Dilnoza (Journals Park Publishing, 2024)
This article provides general conclusions on the analysis of the certification procedure for yogurt products.
Keywords: Yorurt, food, regulation, specifications, bacteria, Inspection, lactose, lactose.